MODEL PENGEMBANGAN DESA WISATA (STUDI KOMPARATIF DESA JAYAGIRI, KECAMATAN LEMBANG DAN DESA SARONGGE, KECAMATAN PACET) - Sutrisno, Budi (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2016)
Tourism development is an effort directed, planned and sustainable, and is influenced by various factors. Therefore, the development of tourism not only need a strategy but also a model that can be applied in accordance with the characteristics of the region. Based on the analysis of the various existing models, most of give attention to regional development and economic aspects (production, distribution and marketing) while giving attention to the macro-structural and cultural environment that affect tourism (social, economic, political, cultural). This model in addition to emphasize the authenticity of which is tourism that takes into account the locality and characteristic regions also emphasize the involvement/participation in tourism development. However, this model also has the disadvantage that does not have a clear stages and steps should be taken to develop an area/region which has the potential for tourism. This model also does not explain how the process of community involvement in self-help in developing tourism as well as components of social capital that can be used. Based on that later drafted a model of the development which is a refinement of the model developed by Nasikun. Models with a pyramid-shaped stages are sequential, starting from organizing society is the core in community empowerment and ending with marketing. The model is built in this paper based on the results of a comparative study that is in Kampung Sarongge which has become a tourist village and village Jayagiri which has the potential to be developed into a tourist village.Keywords: tourism development, tourism pyramid model, tourism village, community